Penyebab Tindak Pidana White Collar Crime - Desi Putri Ani; Maimunah Br Harahap; Nur Sahyani Lubis (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
The aim of this research is to describe the causes of white collar crime. To collect data, this research uses literature study research with secondary data types and qualitative data analysis techniques. The results of the research examined regarding the causes of white collar crime are among professional people who have studied the law in terms of dimensions in the field of work related to seven aspects of people's lives, this involves their expertise in violating the law in order to obtain benefits for themselves and themselves. people involved around him.